PENAMBAHAN PUREE BIT ( Beta vulgari L.) TERHADAP KANDUNGAN GIZI MAKRO DAN KADAR SERAT SOSIS IKAN KEMBUNG (Rastrelliger kanagurt L.) - Ni Kadek Artiningsih (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
The addition of beet puree can be used as a mixture to improve the quality of mackerel fish sausage (Rastrelliger kanagurt L.). Sausage with the addition of beet puree can be a healthy snack for school-age children with adequate macro nutrition and fiber content in mackerel sausage. In this study used a completely randomized design (CRD) including the formulation factor of mackerel and puree beet which consisted of 4 types of treatment repeated 3 times. The results of the analysis were statistically tested using ANOVA 5% and further tested using the Duncan test. The results showed that the use of puree beetroot had a water 71.20-76.66%, ash 1.72-1.81%, fat 9.36-9.61%, protein 9.27-15.80. % and fiber 1.28-1.91%. The contribution of serving 50 grams of sausage in all treatments can contribute to protein intake as much as 8.42-18.85% and fiber intake contributes 2.32-4.20% of the nutritional adequacy rate for school age children 7-12 years. Sausage with the addition of beet puree can be a healthy snack for school-age children with adequate macro nutrition and fiber content.